Long-acting stimulants for treatment of attention-deficit/hyperactivity disorder: a focus on extended-release formulations and the prodrug lisdexamfetamine dimesylate to address continuing clinical challenges - López, Frank A.; Leroux, Jacques R. (Attention deficit and hyperactivity disorders, 2013)
Individuals with attention-deficit/hyperactivity disorder (ADHD) show pervasive impairments across family, peer, and school or work functioning that may extend throughout the day. Psychostimulants are highly effective medications for the treatment of ADHD, and the development of long-acting stimulant formulations has greatly expanded the treatment options for individuals with ADHD. Strategies for the formulation of long-acting stimulants include the combination of immediate-release and delayed-release beads, and an osmotic-release oral system. A recent development is the availability of the first prodrug stimulant, lisdexamfetamine dimesylate (LDX). LDX itself is inactive but is cleaved enzymatically, primarily in the bloodstream, to release d -amphetamine ( d -AMP). Several clinical trials have demonstrated that long-acting stimulants are effective in reducing ADHD symptoms compared with placebo. Analog classroom and simulated adult workplace environment studies have shown that long-acting stimulants produce symptom reduction for at least 12 h. Long-acting stimulants exhibit similar tolerability and safety profiles to short-acting equivalents. While variations in gastric pH and motility can alter the availability and absorption of stimulants released from long-acting formulations, the systemic exposure to d -AMP following LDX administration is unlikely to be affected by gastrointestinal conditions. Long-acting formulations may also improve adherence and lower abuse potential compared with their short-acting counterparts. The development of long-acting stimulants provides physicians with an increased range of medication options to help tailor treatment for individuals with ADHD.